Influence of Wordwall educational games on learning motivation in elementary Pancasila education - Alfitri Rahmadhani; Laili Rahmi (Himpunan Pengembang Kurikulum Indonesia, 2025)
This research is motivated by the low motivation of students to learn and participate in Pancasila Education, particularly in the material on rights and obligations. This is due to the use of learning methods that are less varied and less engaging, involving less active participation from students. To overcome these problems, innovative and interactive learning media are needed, one of which is the use of digital-based educational games, such as Wordwall. The purpose of this study is to determine the effect of the use of Wordwall educational games on the learning motivation of grade IV A SDN 49 Mandau students, Bengkalis Regency. The method used is a pre-experiment with a one-group pretest-posttest design. The research sample consisted of 31 students from Grade IV of SDN 049 Mandau. The research instrument consists of test question sheets administered before and after treatment. Data were analyzed using normality, homogeneity, and a paired sample t-test. The test results showed that the data was distributed normally and homogeneously. The paired sample t-test showed a significant increase in learning motivation after the use of the Wordwall game. The average learning motivation score increased from before to after treatment. Thus, it can be concluded that the use of Wordwall educational games has a positive and significant effect on increasing students' learning motivation in Pancasila Education subjects. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya motivasi belajar peserta didik dalam mengikuti pembelajaran Pendidikan Pancasila, khususnya pada materi hak dan kewajiban. Hal ini disebabkan oleh penggunaan metode pembelajaran yang kurang variatif dan kurang melibatkan partisipasi aktif peserta didik. Sebagai upaya untuk mengatasi permasalahan tersebut, diperlukan inovasi media pembelajaran yang menarik dan interaktif, salah satunya melalui penggunaan gim edukasi berbasis digital seperti Wordwall. Tujuan penelitian ini untuk mengetahui pengaruh penggunaan gim edukasi Wordwall terhadap motivasi belajar peserta didik kelas IV A SDN 49 Mandau Kabupaten Bengkalis. Metode yang digunakan adalah pre-eksperimen dengan desain one group pretest-posttest. Sampel penelitian berjumlah 31 peserta didik dari kelas IV SDN 049 Mandau. Instrumen penelitian berupa lembar soal tes yang diberikan sebelum dan sesudah perlakuan. Data dianalisis menggunakan uji normalitas, homogenitas, dan paired sample t-test. Hasil uji menunjukkan bahwa data berdistribusi normal dan homogen. Uji paired sample t-test menunjukkan adanya peningkatan motivasi belajar yang signifikan setelah penggunaan gim Wordwall. Rata-rata skor motivasi belajar meningkat dari sebelum ke sesudah perlakuan. Dengan demikian, dapat disimpulkan bahwa penggunaan gim edukasi Wordwall berpengaruh positif dan signifikan dalam meningkatkan motivasi belajar peserta didik pada mata pelajaran pendidikan Pancasila. Kata Kunci: gim edukasi; motivasi belajar; sekolah dasar; Wordwall